2021
DOI: 10.1017/s1431927621011946
|View full text |Cite
|
Sign up to set email alerts
|

Fast Grain Mapping with Sub-Nanometer Resolution Using 4D-STEM with Grain Classification by Principal Component Analysis and Non-Negative Matrix Factorization

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(50 reference statements)
2
18
0
Order By: Relevance
“…Its recent success unveils unsupervised techniques as a standard for the processing of high-dimensional datasets, resembling the multimodal crystal phase mapping we described for regular STEM. [130][131][132][133][134][135] Indeed, the mapping of crystal phases and their relative rotations was tested with success in complex oxide systems (e.g., Ti 0.87 O 2 vs. Ti 2 O 3 ) and in dichalcogenide multilayers, such as MoS 2 bilayers. 100,136 Supervised ML has also been proven beneficial for 4D-STEM, as regarded in ptychography.…”
Section: Unsupervised Exploratory Routinesmentioning
confidence: 99%
“…Its recent success unveils unsupervised techniques as a standard for the processing of high-dimensional datasets, resembling the multimodal crystal phase mapping we described for regular STEM. [130][131][132][133][134][135] Indeed, the mapping of crystal phases and their relative rotations was tested with success in complex oxide systems (e.g., Ti 0.87 O 2 vs. Ti 2 O 3 ) and in dichalcogenide multilayers, such as MoS 2 bilayers. 100,136 Supervised ML has also been proven beneficial for 4D-STEM, as regarded in ptychography.…”
Section: Unsupervised Exploratory Routinesmentioning
confidence: 99%
“…Advances in feature representations for 4D-STEM pattern classification have been primarily limited to Bragg disks (BD) (Meng & Zuo, 2017; Pekin et al, 2017; Zeltmann et al, 2020). Recently, principal component analysis (PCA) and NMF were applied to cluster BD from polycrystalline gold nanoparticles into feature sets (Allen et al, 2021). In this work, it was shown that while both NMF and PCA have the ability to reasonably discern grains within nanoparticles, only NMF was able to output results that were directly interpretable as specific orientations due to the non-negativity constraint (Allen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, principal component analysis (PCA) and NMF were applied to cluster BD from polycrystalline gold nanoparticles into feature sets (Allen et al, 2021). In this work, it was shown that while both NMF and PCA have the ability to reasonably discern grains within nanoparticles, only NMF was able to output results that were directly interpretable as specific orientations due to the non-negativity constraint (Allen et al, 2021). This aligns with work in image analysis fields comparing NMF and PCA, where the sparse solution provided by NMF is more readily interpretable than the holistic output that PCA typically provides due to the presence of both additive and subtractive combinations (Lee and Seung, 1999; Guillamet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, we use the individual NBD patterns just for the summation that yields the final PNBD pattern, while ignoring the specific positions and intensities of diffraction spots at each sample location. As the diffraction spots carry the information about the structure and orientation of the investigated material at a given location, the 4D-STEM/PNBD method cannot solve some special problems that are typically addressed by 4D-STEM-in-TEM methods, such as the visualization of different materials in the nanoscale (virtual imaging [28]), the identification of individual phases (structural classification [29]), the analysis of orientation of the individual nanocrystals (orientation mapping [30]), the analysis of strains of the individual nanocrystals (strain mapping [31]) and the enhancement of resolution and/or contrast of the micrographs by means of some advanced techniques (differential phase contrast or ptychography [32]). This is the price paid for the 4D-STEM/PNBD straightforwardness and simplicity.…”
mentioning
confidence: 99%